IMPLEMENTATION OF STAD COOPERATIVE LEARNING MODEL USING GRAPHIC MEDIA IN IMPROVING STUDENTS SOCIAL SKILL OF CIVIC EDUCATION AT THE FOURTH GRADE STUDENTS OF SDN MUNGGU IN THE ACADEMIC YEAR OF 2014/2015 - Nurjanah, Ikhwati (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Abstract: Implementation of STAD Cooperative Learning Model Using Graphic Media in Improving Students Social Skill of Civic Education at the Fourth Grade Students of SDN Munggu in the Academic Year of 2014/2015. The objective is to improve students? social skill of civic education at the fourth grade students of SDN Munggu in the academic year of 2014/2015. This research subjects consist of 28 students. The research is Collaborative-Classroom Action Researchs. This Classroom Action Researchs was conducted in three cycles. Each cycle consists of planning, action, observation, and reflection. Source of data were obtained from students, teacher, colleagues, and researcher. The techniques of collecting data were observation, interview, test, questionnair, and documentation. The result indicates that the implementation of STAD cooperative learning model using graphic media can improve students? social skill of civic education at the fourth grade students of SDN Munggu in the academic year of 2014/2015. Keywords: STAD, Social Skill, Civic Education Abstrak: Penggunaan Model Pembelajaran Kooperatif Tipe STAD dengan Media Grafis dalam Peningkatan Keterampilan Sosial Siswa pada Mata Pelajaran PKn Kelas IV SDN Munggu Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah untuk meningkatan keterampilan sosial pada mata pelajaran PKn Kelas IV SDN Munggu tahun ajaran 2014/2015. Subjek penelitian ini terdiri dari 28 siswa. Penelitian ini merupakan Penelitian Tindakan Kelas kolaboratif. Penelitian Tindakan Kelas ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Sumber data berasal dari siswa, guru, teman sejawat, dan peneliti. Teknik pengumpulan data adalah observasi, wawancara, angket, tes, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran kooperatif tipe STAD dengan media grafis dapat meningkatkan keterampilan sosial siswa pada mata pelajaran PKn Kelas IV SDN Munggu tahun ajaran 2014/2015. Kata kunci: STAD, Keterampilan Sosial, PKn